(untitled) (Numerus academy review, 2026)
This study aims to highlight the functional relationship between the President of the Republic and the Constitutional Court in the area of oversight of the constitutionality of laws The President of the Republic is an active actor in the work of the Constitutional Court through notification, particularly in the area of compulsory control. The latter, in turn, exercises both compulsory and optional constitutional control over the President’s texts, but after being notified of them as a result of its inability to self-notify.